The walking dead. Vol. 15, We find ourselves - Kirkman, Robert (Walking dead (Comic book), 2011)
The events of the previous volume, "No Way Out," have affected everyone in the community, and not everyone has survived to pick up the pieces. Rick and the survivors must now try to pick themselves up and carry in the wake of disaster... and by doing so, they find hope.